1993
DOI: 10.1016/1010-7940(93)90047-f
|View full text |Cite
|
Sign up to set email alerts
|

Retention of bioprosthetic valve annulus in mitral prosthetic replacement

Abstract: Mitral valve prosthetic replacement carries high mortality rates by modern standards, and mitral bioprostheses are particularly prone to degeneration. Bioprosthetic replacement may be technically difficult when there is calcification of the tissue ingrowth, strut incorporation, or valve-to-annulus size mismatch at the primary operation. A "valve-in-valve" technique is described where the mechanical prosthesis is implanted in the bioprosthetic annulus in order to avoid such difficulties. The results in the firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

1996
1996
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 6 publications
0
4
0
1
Order By: Relevance
“…Implantation of a mechanical valve within (valve‐in‐valve) or above (valve‐on‐valve) the sewing ring of the bioprosthetic valve after excision of the valve's leaflets has also been reported (8,9). Implantation of a bioprosthetic valve above the sewing ring has also been performed (10).…”
Section: Discussionmentioning
confidence: 99%
“…Implantation of a mechanical valve within (valve‐in‐valve) or above (valve‐on‐valve) the sewing ring of the bioprosthetic valve after excision of the valve's leaflets has also been reported (8,9). Implantation of a bioprosthetic valve above the sewing ring has also been performed (10).…”
Section: Discussionmentioning
confidence: 99%
“…This technique was described by this team in its first case which was in aortic position [2] . Several reports, later on, were written describing a similar technique in the mitral position [3][4][5][6][7] . In this paper the final modification of valve-on valve or superimposition is described.…”
Section: Discussionmentioning
confidence: 99%
“…However, complete excision of a degenerated and severely adhered mitral bioprosthesis has been reported to be a major source of complications, such as left ventricular rupture, injury of the coronary artery, and fragility of the remaining annulus, which may cause a postoperative paravalvular leak. 3,4 Thus, in patients with degenerated and severely adherent mitral bioprostheses, excising only the bioprosthetic leafl ets and attaching a mechanical prosthesis onto the previously implanted bioprosthetic annulus has been found to be useful. 3,4 This procedure requires exact orifi ce matches.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 Thus, in patients with degenerated and severely adherent mitral bioprostheses, excising only the bioprosthetic leafl ets and attaching a mechanical prosthesis onto the previously implanted bioprosthetic annulus has been found to be useful. 3,4 This procedure requires exact orifi ce matches. Geha et al indicated that an SJM mechanical valve with a diameter ≤2 mm than that of the previously implanted bioprosthesis could be safely implanted.…”
Section: Discussionmentioning
confidence: 99%